The Agility, Adaptation, And Business Optimization, Normal Era For Entrepreneur In Indonesia - Puspitaloka Mahadewi, Erlina; Septyanto, Dihin; Reza Hilmy, Mohamad; Tamzil, Fachmi (International Journal of Science, Technology & Management, 2023)
The present study reports the first comprehensive study about agility, adaptation, and rebuilt the business in new era after covid-19 in Indonesia. Business resilience is very important to achieve the rise of Micro, Small and Medium Enterprises (MSMEs), because of their important role in the national economy. Most business organizations in Indonesia have experienced disruption caused by the covid-19 pandemic, not a few have ended up bankrupt and unable to survive. Businessmen as well as marketers need to manage marketing activities that are adaptive and flexible according to the potential of MSMEs through agile marketing. This research aims to formulate a framework for business revival during and after a crisis like covid-19. This research is expected to provide insights into effective marketing division procedures for business organizations in dealing with business disruptions. A qualitative descriptive approach was used in this study to obtain an overview of the situation experienced by SMEs. Data collection methods used by way of interviews, observation, and documentation, by using purposive sampling method in selecting research sources. Methods of source triangulation and technique triangulation were used in this study to ensure data validation. The data sources for this research are five MSME actors (owners). The results of this study indicate that agile, adaptation, optimization of company business and marketing can be used as solutions to deal with business disruptions in the new normal era. It is hoped in the future that MSMEs can restore their business conditions slowly and be able to revive after the pandemic